2020
DOI: 10.29309/tpmj/2020.27.08.4617
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of pre-diabetes, diabetes mellitus in non-alcoholic fatty liver disease.

Abstract: Objectives: To determine the prevalence of diabetes mellitus and pre-diabetes among patients with NAFLD having BMI ≥ 25 kg/m2and compare it with the control group with non-fatty liver with same BMI. Study Design: Prospective, Analytical and Cross-sectional study. Setting: Department of Medicine, Civil Hospital Karachi. Period: January 2015 to October 2016. Material & Methods: The study was conducted among two groups of patients, one with non-alcoholic fatty liver disease (NAFLD), having BMI of ≥25kg/m2and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…According to numerous research studies, liver infections increased the glycemic level due to producing the insulin resistance but the mechanism is still unknown but the research studies recommend that there is direct interaction of Hepatitis with receptor of insulin via proinflammatory cytokines [9,10]. Ethawary et al had found in HCV sero-positive patients, 13.84% of patients had diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…According to numerous research studies, liver infections increased the glycemic level due to producing the insulin resistance but the mechanism is still unknown but the research studies recommend that there is direct interaction of Hepatitis with receptor of insulin via proinflammatory cytokines [9,10]. Ethawary et al had found in HCV sero-positive patients, 13.84% of patients had diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%